The Diversity of Labuhanbatu Community Culture in Android-Based Applications - Bambang Ade Sulakono; Sumitro Sarkum; Musthafa Haris Munandar; Masrizal Masrizal; Deci Irmayani (International Journal of Advances in Data and Information Systems, 2020)
Android is an application system which has been developed by many people so that people can use the Android system in a work which can help them solve problems in their work. Android systems in smartphones can support complete facilities with Android. Labuhan Batu area is divided into three regions, because of this, knowledge is needed to explains about the culture of the people of Labuhanbatu main district separately of the people in the other districts. In this research, the author describes the research methods used in system design into two parts of method namely the research results obtained by methods using descriptive methods and the research conducted based on actual data by comparing theories and then drawing conclusions. The benefit of the authors working on this research is to make an Android-based application which eases the public to find out the information about the culture that exists in each district in Labuhanbatu Regency. Labuhanbatu Regency Cultural Information Application based on Android can be used by students and even the public, using an Android-based smartphone.